Echo Chambers and Online Radicalism: Assessing the Internet's Complicity in Violent Extremism. Issue 4 (19th April 2015) - O'Hara, Kieron; Stevens, David
Abstract : This article considers claims made by various authors that the use of filtering and recommendation technology on the Internet can deprive certain communities of feedback, and instead amplify groups' viewpoints, leading to polarization of opinion across communities, and increases in extremism. The 'echo chamber' arguments of Cass Sunstein are taken as representative of this point of view, and examined in detail in the context of a range of research, theoretical and empirical, quantitative and qualitative, in political science and the sociology of religion, from the last quarter century. The conclusion is that the case has not been made either (a) that echo chambers are necessarily harmful, or (b) that the Internet is complicit in their formation.